2011
DOI: 10.1007/s11340-011-9463-6
|View full text |Cite
|
Sign up to set email alerts
|

In-situ AFM Experiments with Discontinuous DIC Applied to Damage Identification in Biomaterials

Abstract: Natural materials (e.g. nacre, bone, and spider silk) exhibit unique and outstanding mechanical properties. This performance is due to highly evolved hierarchical designs. Building a comprehensive understanding of the multi-scale mechanisms that enable this performance represents a critical step toward realizing strong and tough bio-inspired materials. This paper details a multi-scale experimental investigation into the toughening mechanisms in natural nacre. By applying extended digital image correlation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…For instance, studies performed on abalone nacre revealed that the material exhibits a toughness similar to aluminum even when it contains 95% calcite, a ceramic . Espinosa and co‐workers showed that such toughness arises from a millimeter size process zone consisting of tablets sliding without pullout . Recent developments in advanced manufacturing such as freeze casting and 3D printing have made possible the direct translation of the elegant architectures from natural materials to artificial materials and structures.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies performed on abalone nacre revealed that the material exhibits a toughness similar to aluminum even when it contains 95% calcite, a ceramic . Espinosa and co‐workers showed that such toughness arises from a millimeter size process zone consisting of tablets sliding without pullout . Recent developments in advanced manufacturing such as freeze casting and 3D printing have made possible the direct translation of the elegant architectures from natural materials to artificial materials and structures.…”
Section: Introductionmentioning
confidence: 99%
“…The plot shows a short development phase during which the process zone attains its final width of ≈0.4 mm. Previously, the process zone of nacre has been studied by observing the whitening zone at the crack tip that provides clear indication of platelet sliding taking place . Therefore, the speckle imaging can be compared against the traditional method for verification.…”
mentioning
confidence: 52%
“…Small scratches of specimen surface were artificially made by mechanically polishing the surface using the 4000-grit sandpaper. The difference in the positions of small scratches on surface of sample before and after deformation was used to quantify the local strain38. Additionally, the strain distributions were analyzed using the VIC-2D software.…”
Section: Methodsmentioning
confidence: 99%